On hyperideals of Krasner hyperrings based on derived unitary rings - Seyed Shahin Mousavi; Morteza Jafarpour; Hojat Babaei; Irina Cristea (Journal of Mahani Mathematical Research)
In this paper first, we introduce and analyze the strongly regular relations $λ^*_{e}$ and $Λ^*_{e}$ on a hyperring such that the derived quotient ring is unitary and unitary commutative, respectively. Next, we define and study the notion of $λ_e$-parts in a hyperring and characterize the $λ_e$-parts in a $λ_e$-strong hyperring $R$. Finally, we introduce the notion of $λ_e$-closed hyperideal in a hyperring and study some of its fundamental properties in Krasner hyperrings.